Peran Strategi dan Mindset Kewirausahaan dalam Menghadapi Tantangan di Era Digital - Nur Aida Basir; Rachmad Arief Sunaryo; Raihan Dary Wiguna; Surya Hari al Amin S; Wahyu Bimantara Hadi S; Feti F (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
The digital era has fundamentally transformed how businesses operate, compete, and create value. Rapid technological advancements, digital platforms, and changing consumer behavior have forced entrepreneurs to continuously adapt in order to remain relevant and competitive. Modern entrepreneurship therefore requires not only adaptive and flexible strategies but also an innovative and growth-oriented mindset to effectively navigate the challenges and opportunities brought by digital transformation. This article aims to examine the role of entrepreneurial strategies and mindsets in managing organizational change, fostering continuous innovation, and enhancing business competitiveness in the digital age. This study employs a qualitative research approach using a literature review method, drawing on various theoretical frameworks and empirical studies related to entrepreneurship, digital transformation, and innovation. The findings indicate that a digital-based entrepreneurial strategy, supported by an adaptive and proactive entrepreneurial mindset, plays a crucial role in enhancing innovation capacity, improving decision-making, and strengthening business resilience in the face of technological disruption and market uncertainty. Furthermore, the integration of digital technologies enables entrepreneurs to identify new business opportunities and improve operational efficiency. The findings of this study are expected to serve as a valuable reference for policymakers, academics, and practitioners in advancing the development of digital entrepreneurship, particularly in the context of Indonesia.